PENGARUH PERKEMBANGAN GUNA LAHAN TERHADAP KINERJA RUAS JALAN ARTERI PRIMER DI KABUPATEN SIDOARJO - , Eko Andrianto, Arief Setiawan Budi Nugroho, ST, M.Eng, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Population and economic growth which is significant in Surabaya resulted in the availability of land that is no longer able to meet the needs of residents of the city of Surabaya. It has an impact on the development of land use in Sidoarjo which bordered by Surabaya. The development of the land use resulted in increased intensity of significant movement on primary arterial roads between the city of Surabaya to Sidoarjo regency, thus affecting the performance of these roads. The data analyzed in this study of secondary data between the years 2008-2012 in the form of data types and extensive land use, population, traffic flow and geometric path obtained from the relevant authorities. To determine the relationship and influence the development of residential land, industrial-warehouse, public facilities, etc., and the number of people on the road performance with value vcr (volume capacity ratio) and speed as its parameters were calculated using Pearson product moment correlation analysis, the double correlation, partial correlation and multiple linear regression backward method. The relationship between the vcr entire roads in the study area in a unity there is a strong significant relationship with the development of residential land use and industrial-warehouse with a correlation coefficient values respectively 0.779 and 0.612. Influence the development of residential land, industrial-warehouse, public facilities and the number of people on the roads in the entire study area is reviewed in a single, influential in determining the change in the value of determination of vcr with 76.1 %